Migração e família: a dinâmica familiar de guianenses na cidade de Boa Vista-RR - Lima, Arieche Kitiane Silva (2014)
This dissertation has as object the family relationships of Guyanese who migrated to the city of Boa Vista/RR. Addresses the issue of international displacement of populations of countries in the Pan-Amazon, in particular the implications of this phenomenon in family relationships both in the host location as other relatives residing in other countries such as the Cooperative Republic of Guyana, the USA and Canada. In this context, we sought to identify, family arrangements, transnational experiences and other strategies that pervade the family ties during the migration process. We used a qualitative methodology, with emphasis on participant observation, open interviews and informal conversations. The interlocutors of the study were men and women of Guyana nationality who went in different periods and carrying different business activities. While they are away from their place of origin, it was identified that the organization attempts to Guyana group are located in meetings with friends on religious activities and localized meetings. The narratives of the interlocutors demonstrate the existence of vulnerabilities related to skin color, obtaining employment and language learning, on the other hand the existence of family networks in the host locality is essential for fixing the migrant and the redefinition of family roles and establishment of new arrangements in the family.